Late Oligocene Larger Foraminifera From Nosara (Nicoya Península, Costa Rica) and Indward (Carriacou, Lesser Antilles), Calibrated by 87sr/ 86sr Isotope Stratigraphy - Baumgartner-Mora, Claudia (Universidad de Costa Rica, 2007)
.